Rapid Generation of Murine Bispecific Antibodies Using FAST-IgTM for Preclinical Screening of HER2/CD3 T-Cell Engagers - Hikaru Koga; Haruka Kuroi; Rena Hirano; Hiroyuki Hirayama; Yoshiaki Nabuchi; Taichi Kuramochi (Antibodies, 2024)
Bispecific antibodies (BsAbs) can bind to two different antigens, enabling therapeutic concepts that cannot be achieved with monoclonal antibodies. Immuno-competent mice are essential for validating drug discovery concepts, necessitating the development of surrogate mouse BsAbs. In this study, we explored the potential of FAST-IgTM, a previously reported BsAb technology, for mouse BsAb production. We investigated charge-based orthogonal Fab mutations to facilitate the correct assembly of heavy and light chains of mouse antibodies and employed knobs-into-holes mutations to facilitate the heterodimerization of heavy chains. We combined five anti-CD3 and two anti-HER2 antibodies in mouse IgG1 and IgG2a subclasses. These 20 BsAbs were analyzed using mass spectrometry or ion exchange chromatography to calculate the percentages of BsAbs with correct chain pairing (BsAb yields). Using FAST-Ig, 19 out of the 20 BsAbs demonstrated BsAb yields of 90% or higher after simple protein A purification from transiently expressed antibodies in Expi293F cells. Importantly, the mouse BsAbs maintained their fundamental physicochemical properties and affinity against each antigen. A Jurkat NFAT-luciferase reporter cell assay demonstrated the combined effects of epitope, affinity, and subclasses. Our findings highlight the potential of FAST-Ig technology for efficiently generating mouse BsAbs for preclinical studies.